Solving Cases of Historical Justice: How Lithuanians Defended Their Tribe - Lastauskienė, Giedrė (Teisė, 2021)
The article raises the problem of the distinction between the law and laws arising from changes in legal order or other fundamental social changes. The legal doctrine and case-law relating to cases of historical (transit) justice are examined in the context of the examples of Germany and Lithuania. Under investigation is the model of punishment of persons who collaborated with Soviet occupiers and contributed to the elimination of participants of the resistance movement, implemented in Lithuania, revealing the factors influencing the change in this model.